Six Sigma evaluation using process capability and -X control chart for reducing variance in oil density characteristic: a study in Yemen. (2017) - Ali, Faisal A.M.; Ahmed, Amran
This paper presents Six Sigma evaluation based on process capability with -X control chart to reduce variations in the oil density characteristics in an oil refinery process in Aden, Yemen. Twenty-five oil density samples with normal distribution were randomly collected, and each sample consisted of four items. Analysis indicated that the levels of sigma employed in Aden refinery are less than 3 σ. The results of this study suggested that the -X chart based on six sigma estimation method is significant to reduce variance in the oil density characteristic. In addition, the sigma levels increase when the process capability increases. Thus, the increment in sigma levels leads to improvements in the performance of the process refinery of oil density characteristic. Finally, this paper provides the necessary fundamentals and knowledge for quality control researchers and engineers to reduce variances by using Six Sigma.